Evaluation of Hearing Status in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Observational Study - Dhasmana, Gunjan; Singh Bist, Sampan; Kumar, Lovneesh; Modi, Sagar; Kumar Agarwal, Vinish; Kumar Mittal, Himanshu (ENT Updates, 2021)
Objective: Hearing loss as a complication of diabetes is a debatable issue with a handful of contradictory studies. The objective of the present study was to evaluate the status of hearing in patients with type 2 diabetes mellitus and to correlate the severity of hearing loss with the duration of diabetes mellitus. Methods: This is an observational cross-sectional study which was done at a tertiary care teaching hospital over a period of 12 months. Two hundred consecutive type 2 diabetic patients in the age group between 18 and 60 years were enrolled. Patients were subjected to blood sugar levels, glycosylated hemoglobin, and pure tone audiometry. Possible confounders for hearing loss were excluded. The chi-square test was applied and P < .05 was considered significant. Results: The average age of the patients was 47.18±8.65 years with a male to female ratio of 1.19 : 1. The mean duration of diabetes was 5.60±4.15 years. Out of 200 patients, hearing loss was observed in 55%. The prevalence of sensorineural hearing loss was 50%. Higher frequencies (4 kHz-8 kHz) were most affected. The association of fasting blood sugar and HbA1c levels with hearing loss was significant while no association was observed between the duration of diabetes and hearing loss. Conclusion: The study confirmed hearing loss in almost half of the diabetic patients while no association was observed between the duration of diabetes and hearing loss. It is recommended that the audiological screening must be included in the initial evaluation of the diabetic patient to detect and prevent further hearing loss.